The word Jondē Šāpur; its meaning and significance - شهرام جلیلیان (پژوهش‌های تاریخی ایران و اسلام, 2012)
Sasanians were the great builders of cities and the extension and importance of building cities in Sasanian epoch were reflected in historical and geographical texts. Based on historical accounts, Šāpur I (241-272 A.D), returning from his victorious battles against the Roman empire, settled the captives and deportees of Antioch in Xuzestan in a new built city called “Weh-Az-Andiōk-Šābuhr”which means “Šāpur’s city better than Antioch”. On his inscription on the Ka’be-ye Zardosht, Šāpur called this city “why-’ndywk-Šhypwhr-y”(Weh-Az-Andiōk-Šābuhr), but in the Greek text of that inscription it was written as “Gove-Antioch-Sābur”, which like other names that begin with Iranian “w”, this “w” is replaced by “g”. In Islamic historical and geographical texts this city is called “Weh-Az-Andiō-Šāpur”, “Andiō Šāpur”, “Gondē Šāpur”, “Jondē Sābur”, or “Jondē Šāpur”. The meaning of the word “Gund” in middle Persian was “army” and in Arabic language “Jund” has the same meaning as “Gund”, so it was erroneously assumed that the meaning of Gondē Šāpur /Jondē Šāpur was “Šāpur’s military fortress”. In fact Jondē Šāpur, is the Arabicized form of the Greek pronunciation of the name of this city and is not related to “Gund” and “Jund” that means “army” or “military fortress”. Although all historical accounts show that Jondē Šāpur was built in the reign of Šāpur I and show that its name is related to the name of Šāpur I, and archeological excavations in the hills of south of Šāhābād, a village situated 14 km southeast of Dezful, that must have been the site of the Sasanian Jondē Šāpur, reveal that Jondē Šāpur was a new built city in Sasanian era and there is no evidence to related it to pre-Sasanian era, but some researchers erroneously believe that Jondē Šāpur dates from prehistoric periods and the word Jondē Šāpur is the changed form of the Indian word “Gentāšāpirtā” which means “beautiful garden” or “beautiful city”! Studying the history of Jondē Šāpur different views about the meaning of the word Jondē Šāpur, this paper aims at giving the true meaning of this word.